Implementasi Kebijakan Inovasi Pelayanan Kesehatan Berbasis Home Care di RSUD Dr. Thomsen Nias - Iman Ridho Purnama Mendrofa; Ayler Beniah Ndraha; Fatolosa Hulu; Eliagus Telaumbanua (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study examines the implementation of home care-based health service innovations at Dr. M. Thomsen Nias Regional General Hospital as an adaptive strategy to overcome limited access to services in island regions. The aim is to analyze the benefits, challenges, and strategies for strengthening the program, with a focus on human resource management aspects. The research method employs a descriptive qualitative approach through in-depth interviews, participatory observation, and documentary studies involving relevant stakeholders. The results indicate that home care significantly improves accessibility for vulnerable groups, reduces geographical barriers, and enhances the quality of interaction between healthcare workers and patients. The program's success is influenced by visionary leadership, selective recruitment, continuous training, and sustained work motivation. However, challenges such as high workloads, logistical limitations, and suboptimal cross-unit coordination remain. The implications of this research emphasize the importance of institutional strengthening, the establishment of a dedicated home care unit, the use of information technology, and cross-sector collaboration based on local values to ensure the sustainability of the program and improve the health status of communities in remote areas. Furthermore, this study underscores the importance of continuously evaluating the performance of home care services through measurable indicators based on local needs. Routine monitoring and active community involvement as beneficiaries can increase accountability and encourage participation in maintaining service continuity. Strengthening an organizational culture that is adaptive and responsive to changes in the external environment is also key to anticipating the dynamic health needs of island communities. Thus, the home care approach is not merely a short-term solution but also part of the transformation of the health care system toward a more inclusive and socially just model.